x
−
3
y
=
5
,
x
+
5
y
=
−
3
Add
3
y
to both sides of the equation.
x
=
5
+
3
y
x
+
5
y
=
−
3
Replace all occurrences of
x
with the solution found by solving the last equation for
x
. In this case, the value substituted is
5
+
3
y
.
x
=
5
+
3
y
(
5
+
3
y
)
+
5
y
=
−
3
Solve for
y
in the second equation.
Tap for more steps...
x
=
5
+
3
y
y
=
−
1
Replace all occurrences of
y
with the solution found by solving the last equation for
y
. In this case, the value substituted is
−
1
.
x
=
5
+
3
(
−
1
)
y
=
−
1
Simplify
5
+
3
(
−
1
)
.
Tap for more steps...
x
=
2
y
=
−
1
The solution to the system of equations can be represented as a point.
(
2
,
−
1
)
The result can be shown in multiple forms.
Point Form:
(
2
,
−
1
)
Equation Form:
x
=
2
,
y
=
−
1